Genetic Engineering and The Non-Identity Problem (Diametros, 2013)
In my essay I consider the imaginary case of a future mother who refuses to undergo genetic alteration on her germline although she knows that her, as yet unconceived, child will have a serious genetic disorder. I analyze the good and bad points of two branches of arguments directed against her decision, consequentialist and rights-based. Then I discuss whether accepting one line of these arguments or the other makes a difference in moral assessment. I conclude that, although from the preanalytical perspective we strongly oppose the refusal of genetic treatment in my imaginary case, it is probably impossible to construct one coherent theory which embraces all possible moral dilemmas triggered by our actions which affect the number and the identity of future people.